Binder-free bonding of modularized MXene thin films into thick film electrodes for on-chip micro-supercapacitors with enhanced areal performance metrics. Issue 30 (18th July 2018) - Hu, Haibo; Bai, Zhiman; Niu, Ben; Wu, Mingzai; Hua, Tao
Abstract : An efficient and easily-manipulated protocol was developed to prepare binder/conductive-additives free thick MXene film electrodes through bonding the modularized thin films only with water. The thickness can be multiplied by increasing the number of superposed modularized thin MXene films. Abstract : Areal capacitance and energy density are highly important performance metrics for on-chip micro-supercapacitors (MSCs) with limited footprint area. Unfortunately, both of them are still far from satisfactory due to the low specific capacitance of traditional carbonaceous electrode materials and minor electrode thickness. Employing MXene pseudocapacitive materials with high conductivity and competitive specific volumetric capacitance to fabricate binder/conductive-additive free thick film electrodes is considered to be a promising approach to improve the poor areal performance metrics of on-chip MSCs. However, it still proves to be a great challenge, especially for fully delaminated single- or few-layered MXene flakes. Herein, aiming at addressing the challenge, an efficient, easily manipulated but ingenious protocol was developed to enable the preparation of binder/conductive-additive free thick MXene film electrodes through bonding modularized thin MXene films consisting of fully delaminated few-layered MXene flakes only with water, whose thickness can be multiplied simply by increasing the number of superposed modularized thin MXene films. Following a laser-cutting pattern process, on-chip MSCs with an areal capacitance of up to 71.16 mF cm −2 can be fabricated, which is at least seven times higher than those of carbon materials based on-chip MSCs (0.1–10.0 mF cm −2 ) and obviously enhanced compared to those of the few reported state-of-the-art MXene-based on-chip MSCs (4.2–61.0 mF cm −2 ). The interesting binder-free bonding method combined with a laser-cutting technique enables the fabrication of thick MXene-based coplanar interdigital electrodes for on-chip MSCs in a fast and efficient manner while achieving excellent areal performance metrics, making them promising built-in micropower sources for maintenance-free microelectronic devices.